Informação de validade de produtos alimentícios: avaliação do conhecimento e comportamento dos consumidores no Ceará - Silva, Karoline Rodrigues dos Santos (2023)
The consumption of processed foods is advancing, to regulate them, ANVISA determines the labeling standards for these products and the expiration date is an important tool for consumers when purchasing and to preserve their health. In this context, a bibliographical survey was carried out on the definitions of the expiration date, its influence on consumer health and its relationship with waste, methods for its determination, legal aspects involved in Brazil and global scenario. Based on the bibliographic study, a survey was carried out in the State of Ceará, assisted by the Google Forms platform, to qualitatively analyze consumers in relation to the expiration date. It is presumed that the expiration date of food products is important for protecting the health of consumers due to possible changes in general features, which are evaluated to determine the period, it is a labeling item that has not undergone major changes since its inclusion in the laws that involve labeling, it has been observed that there are great differences in dealing with the expiry date of food products in other countries. In Ceará, consumers are careful when shopping, however they experience difficulties in checking the expiration date, they benefit from products on offers with critical dates and at home they consume expired products relying on sensory experiences, in addition, they are not well aware of the standards legal guidelines about validity, which may lead to misinterpretations. Therefore, it is advisable to reflect on new updates to Brazilian standards to assist consumers.